The Immediate Adverse Events of Lumbar Interventional Pain Procedures in 4,209 Patients: An Observational Clinical Study - (:unkn) unknown (OXFORD UNIV PRESS, 2022)
Objective. Lumbar interventional pain procedures (LIPPs) are frequently used in low back pain and have shown an increasing trend in recent years. LIPPs are highly effective when performed by properly trained physicians. However, some adverse events are seen during interventional procedures. Our aim in this study is to determine the immediate adverse event rates of LIPPs and to inform our colleagues about possible adverse events. Study Design. Retrospective, observational study. Setting. A university hospital pain management center. Methods. After approval by the institutional ethics committee, a retrospective evaluation of patients who received fluoroscopy-guided LIPPs between January 2015 and December 2020 was performed. This observational study was conducted with 4,209 patients who underwent LIPPs, including epidural steroid injection, sacroiliac and facet joint injection, medial branch block or radiofrequency ablation, application of pulsed radiofrequency to the dorsal root ganglion, epidural catheter placement, or spinal cord stimulator application. Results. No major adverse events were detected during the procedures. Minor adverse events were detected in 60 patients, and the adverse events rate was found to be 1.4% (95% confidence interval: 1.0-1.8%). Minor adverse events rates varied between 0.7% and 2.3% according to the procedure type. The most common adverse events were determined to be vasovagal reactions (26/60). Facial numbness, cramps, and seizures were detected as rare adverse events. Conclusion. No major adverse events were seen in 4,209 patients. The rate of minor adverse events was 1.4%, with no sequelae in any of the events. When evidence-based guidelines are followed, interventional pain procedures can be performed safely.
Keywords: Spine; Lumbar; Back Pain; Fluoroscopy; Safety; INJECTION; EFFICACY